Penerapan Lean Operation Guna Meminimalkan Produk Cacat Menggunakan Metode PDCA - Arief Setyani Komara Sugama, Arief Setyani Komara (LPPM Universitas PGRI Adi Buana Surabaya, 2021)
Increasingly complex global competition, uncertain customer demands, and increasing customer expectations are the driving forces in implementing more optimal productivity such as the lean operation. In carrying out its operational activities, the company’s production process has not been able to run efficiently due to waste of defective products. This study uses primary and secondary data. This study also uses observation and documentation data collection method. To implement lean operation, the PDCA method is used which supported by tools such as the seven basic tools of TQM, VSM, and FMEA. By implementing the lean operation, it has been proved to reduce the number of defective products. For ODAKPR products, defects from overlock results are not paralleled decreased 72,95% to 102 pieces, perforated overdeck stitches decreased 76,42% to 75 pieces, misalignment of labels decreased 78,15% to 52 pieces. For OJAKPR products, defects from overlock results are not paralleled decreased 62,40% to 97 pieces, perforated overdeck stitches decreased 69,06% to 69 pieces, misalignment of labels decreased 73,77% to 48 pieces. For CJPPR products, defects of overdeck suture distance decreased 65,80% to 92 pieces, misalignment of labels decreased 76,76% to 56 pieces, overlock results are not paralleled decreased 77,96% to 41 pieces.